Determinan dari Harga Saham pada Perusahaan Perbankan di Bursa Efek Indonesia - Nuddin, Muhammad Farhan; Damayanti, Damayanti (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This study aims tol determinated the effect of Net Profit Margin (NPM), Earning Per Share (ElPS), and Return on Asset to stock price. The population in this research are 40 banking companiess listed on Indonesian Stock Exchange (IDX) from 2018-2022. This research using purposive sampling and obtained a sample of 27 companies using the method of documentation, thel uses of data derived from documents that already axist and publish in Indonesian Stock Exchanges website. Data analysis using multiple regression. Result of the analysis indicated that net profit margin has no significant positive effect on stock price, earning per share has a positive significant effect on stock price, return on asset has a no significant negative elffect on stock price. the adjusted R2 value is 0,338, it means that 33,8% of the variation in the stock prices of banking companies listeld on thel Indonesian Stolck Exchange can be explained by the three independent and dependent variables. While the remaining 66,2% is explained by other variables not elxamined in this research model. Keywords: Net Profit Margin, Earning Per Share, Return on Asset and stock price.